Surgical Hand Washing – A Clinical Audit of Young Surgeons at a Tertiary Care Hospital - Fahad Hussain, Muhammad Khalil ur Rahman, Haseeb Mehmood Qadri, Rana Arslan Rabbani (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Surgical hand washing is the most important preliminary step towards an aseptic surgical approach while dealing the patients. The surgeons know the significance of asepsis, but still they fail to follow the steps of an ideal surgical scrubbing and hand washing technique. Aim: To assess the compliance of standard surgical practices of hand washing technique among young surgeons. Methods: A total of 30 surgical residents were assessed for the compliance of standard surgical practices of hand washing technique randomly. Interventions were made to improve the mistakes and malpractices and inporive the compliance rates of the World Health Organization (W.H.O.) criteria. Data was collected on a computer generated questionnaire. Data was analyzed using the S.P.S.S. 26 version. Results: Only 63% resident surgeons were compliant in following the standard hand washing technique. After intervention, the rates increased to 90.3%. The 30-35 years age group had the best compliance rates. Conclusion: Repeated audits, timely interventions and senior supervisison of the surgical residents regarding the surgical scrubbing and hand washing technique can reduce the malpractices to a minimum level. There is a huge gap in the usual practitces and standard practices.